Some like it hot: Assessing longer-term labor market benefits from a high-pressure economy - Julie L. Hotchkiss; Robert E. Moore (Federal Reserve Bank of Atlanta, 2018)
This paper explores the evidence for positive hysteresis in the labor market. Using data from the National Longitudinal Surveys of Youth, we find that negative labor market outcomes during high-unemployment periods are mitigated by exposure to a high-pressure economy during the preceding expansion. Breaking total exposure into average intensity and duration suggests that these two dimensions have differing impacts depending on the outcome. Additionally, benefits are typically only statistically significantly different from no exposure for only a relatively few demographic groups.
Keywords: E60; E24; J64; J31; 330; hysteresis; unemployment; labor market gaps; labor force participation; wage gaps